Technical Analysis of Oil of Transformers Working in LongTerm Operation - F.A.Khalilova; U.Z.Abdurashidov (Genius Journals, 2023)
The article discusses the influence of transformer oil on energy saving during operation. The properties of transformer oil and changes in their parameters are described. At the same time, the role of transformer oil in the heat exchange process, the equipment in which it can be used, the factors influencing the change in the physical parameters of the composition and composition are described.
Keywords: Liquid dielectric; electricity; heat